Health Care Reform in Massachusetts: Implementation of Coverage Expansions and a Health Insurance Mandate - Doonan, Michael T (Blackwell Publishing Inc, 2010)
Context: Much can be learned from Massachusetts's experience implementing health insurance coverage expansions and an individual health insurance mandate. While achieving political consensus on reform is difficult, implementation can be equally or even more challenging. Methods: The data in this article are based on a case study of Massachusetts, including interviews with key stakeholders, state government, and Commonwealth Health Insurance Connector Authority officials during the first three years of the program and a detailed analysis of primary and secondary documents. Findings: Coverage expansion and an individual mandate led Massachusetts to define affordability standards, establish a minimum level of insurance coverage, adopt insurance market reforms, and institute incentives and penalties to encourage coverage. Implementation entailed trade-offs between the comprehensiveness of benefits and premium costs, the subsidy levels and affordability, and among the level of mandate penalties, public support, and coverage gains. Conclusions: National lessons from the Massachusetts experience come not only from the specific decisions made but also from the process of decision making, the need to keep stakeholders engaged, the relationship of decisions to existing programs and regulations, and the interactions among program components.